Does Gender Influence Physiological Tolerance in Resuscitators When Using Personal Protection Equipment against Biological Hazards? - Francisco Martín-Rodríguez; José Luis Martín Conty; Verónica Casado Vicente; Pedro Arnillas Gómez; Alicia Mohedano-Moriano; Miguel Ángel Castro Villamor (Emergency Medicine International)
Introduction. Certain professions, such as those related to emergency services, have usually been performed by men, progressively incorporating women into these professions. The main objective of our study was to determine, according to gender, how the use of level D biohazard personal protection equipment (PPE) affects emergency professionals during the performance of resuscitation. Materials and Methods. An uncontrolled quasi-experimental study was performed on 96 volunteers selected by means of random sampling stratified by gender. Baseline and final vital signs of the assessment activity were analyzed. This activity involves volunteers performing a simulated resuscitation in a controlled environment whilst wearing personal protective suits in a biohazard situation. Results. Analyzing the physiological tolerance pattern parameter by parameter, and according to gender, through a univariate model, we can observe that there is no interaction between tolerance and gender; that is, having good or bad tolerance does not depend on gender. Conclusion. This specialized skilled work can be performed by any properly trained professional.